PENGEMBANGAN KAPASITAS KELEMBAGAAN DALAM KOORDINASI PELAYANAN PERIZINAN DI BPPT KOTA SEMARANG - Pratama, Ardie; Mustam, Muhammad; Djumiarti, Titik (Journal of Public Policy and Management Review, 2014)
For service delivery to the community and increase regional competitiveness required capability or capacity of local governments adequate. Development of local government capacity always contains an understanding of the various efforts to improve the performance of services to the community. This study aims to describe the development of institutional capacity and supporting factors and obstacles encountered in the development of institutional capacity at the Integrated Licensing Service Agency of Semarang. This research uses descriptive study with a qualitative approach. The focus of the study include: (1) development of institutional capacity at the Integrated Licensing Service Agency of Semarang, (2) factors to be supporting and institutional capacity building. Results of this study was the development of institutional capacity in the Integrated Licensing Service Agency of Semarang still needs to be improved further in the aspect of organizational structure, work procedures, human resources, budget, facilities. Advice given is the Integrated Licensing Service Agency of Semarang to be more innovative in the development of institutional capacity.